2022
DOI: 10.21203/rs.3.rs-2186982/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The stability of dams with different stoping elevations in Tongling valley type tailings impoundment: A case study in Yunnan China

Abstract: Significant interest has been focused on recovery rates, recovery options, and recovery utilization when tailings impoundments are re-mined. However, the stability of the tailings dams during the recovery process is also a severe issue. Based on engineering geological survey and laboratory tests, the Tongling tailings impoundment’s characteristics of instability evolution under different recovery heights and diverse working conditions were analyzed by numerical simulation. Firstly, with the help of 2D software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Wang [51] studied the release and migration law of heavy metals in tailings ponds and found that the concentration of Cd decreased with the leaching time. The heavy metal Cd concentration decreased rapidly at the initial leaching stage, slowing down during the later stage, which was consistent with the results in this paper.…”
Section: The Characteristics and Factors Influencing CD Leaching In Soilmentioning
confidence: 99%
“…Wang [51] studied the release and migration law of heavy metals in tailings ponds and found that the concentration of Cd decreased with the leaching time. The heavy metal Cd concentration decreased rapidly at the initial leaching stage, slowing down during the later stage, which was consistent with the results in this paper.…”
Section: The Characteristics and Factors Influencing CD Leaching In Soilmentioning
confidence: 99%